Evaluasi Dampak Pembangunan Pembangkit Listrik Tenaga Sampah Benowo Oleh Kolaborasi Pemerintah - Swasta dalam Lingkungan Masyarakat Kelurahan Sumberrejo Kecamatan Pakal Kota Surabaya - Ricky Satya Panjalu; Achluddin Ibnu Rochim; Indah Murti (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
The impact of a policy can occur outside the wishes of the policy formulator or commonly called unexpected impacts. PLTSA Benowo is the result of collaboration between the Surabaya City Government and PT Sumber Organik and is equipped with gasification power plant technology which is regulated in PERPRES No. 35 of 2018. This PLTSA policy is a form of handling the national waste problem, such as eliminating waste and providing socio-economic benefits in the vicinity. The purpose of this study was to analyze and describe how the evaluation of the impact that occurred from the PLTSA development policy on the community of Sumberrejo Village, Pakal District, Surabaya City. The research method in this study uses descriptive qualitative methods, for data collection through observation, documentation, and observation. The results of this study show 3 indicators including Individual Impact shows the positive impact of PLTSa for the Community economically, while the negative impact shows that it is not disturbed from the remaining emissions from the waste combustion process released by PLTSa Benowo. Community Impact The positive impact shows that it affects the increase in the economy of the wider community of Sumberrejo Village, while the negative impact is that the community feels an increase in air pollution that disturbs the comfort of the community due to air pollution from PLTSa Benowo. Social System Impact The positive impact shows a change in the social system in the community because there is an increase in economic structure and a reduction in unemployment, while the negative impact shows there is an indication of social inequality such as feelings of envy from people who do not get economic benefits from PLTSa to people who get economic benefits from PLTSa Benowo.